Quranic TQM Philosophies and Principles: The Basis of an Islamic Welfare State - Khan, Nawar (Journal of Islamic Thought and Civilization, 2024)
The purpose of this research study is to establish the relationship, precedence order, and scope and application comparison between the Modern TQM knowledge as so-called by the modern societies of the world and the already existing Quranic TQM wisdom to bridge the gap among different religions and schools of thought.The terms modern, latest, and advanced philosophies, principles, and terminologies are continuously being coined in literature around the world across every field of business, socio-cultural, and economics, etc. CQI philosophy is the basic essence of the Modern TQM. Modern TQM is bound to a company’ business and focuses mainly on the profit generation. The Quranic TQM philosophies and principles encompass life and living in total (mindset, spiritual, religious, cultural, social, economic, and physical etc) here and in the hereafter, rather than being confined to business concerns only. Hence, its main focus is the welfare and well-being of the society and humanity. The aim for this research is to fill the gap that exists between the holistic Quranic TQM knowledge base and the Modern TQM knowledge and scientific exploration. Filling the gap mean to establish its relationship, the precedence order, size of scope and then compare the two TQM. An exploratory and qualitative research methodology is used to study, identify, analyze, and discuss the traces of the relationship, precedence order, scope and application comparison of the modern TQM philosophies and principles with Quranic TQM philosophies and principles of divine knowledge.